Assessing lifetime stressor exposure in sport performers: Associations with trait stress appraisals, health, well-being, and performance. (January 2022) - McLoughlin, Ella; Arnold, Rachel; Fletcher, David; Spahr, Chandler M.; Slavich, George M.; Moore, Lee J.
Abstract: Research has found that greater lifetime stressor exposure increases the risk for mental and physical health problems. Despite this, few studies have examined how stressors occurring over the entire lifespan affect sport performers' health, well-being, and performance, partly due to the difficulty of assessing lifetime stressor exposure. To address this issue, we developed a sport-specific stress assessment module (Sport SAM) for the Stress and Adversity Inventory (STRAIN) and then analyzed the instrument's usability, acceptability, validity, and test-retest reliability. Furthermore, we examined whether trait-like tendencies to appraise stressful situations as a challenge or threat mediated the association between lifetime stressor exposure and health, well-being, and performance. Participants were 395 sport performers ( M age  = 22.50 years, SD  = 5.33) who completed an online survey. Results revealed that the Sport SAM demonstrated good usability and acceptability, good concurrent validity in relation to the Adult STRAIN ( r s = 0.23 to 0.29), and very good test-retest reliability ( r icc  = 0.87 to 0.89). Furthermore, the Sport SAM was significantly associated with symptoms of depression ( β  = 0.21 to 0.24, ps  ≤ .001) and anxiety ( β  = 0.13 to 0.19, ps  ≤ .012), and general physical ( β  = 0.24 to 0.27, ps  = ≤ 0.001) and mental ( β  = 0.23 to 0.32, p  ≤ .001) health complaints. Finally, we found that associations between total lifetime non-sport and sport-specific stressor severity and health were mediated by trait stress appraisals. Consequently, these findings may help practitioners better identify sport performers who are at risk of developing stress-related health problems. Highlights: This study developed a measure to assess sport-specific lifetime stressors. Greater lifetime (sport-specific) stressors predicted poorer mental and physical health. Greater lifetime (non-sport) stressors predicted poorer health and well-being. The stressor severity-health relationship was mediated by trait stress appraisals.